Implementasi Model View Controller (MVC) Pada Sistem Informasi e-Pustaka - Aziz, Muhammad Abdul; purbasari, Yuntari; Fajriyah, Fajriyah (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
One form of technology that can be utilized in libraries is the e-library information system. An e-library information system is used to organize book collections so that they are neater, safer, easier to manage, and can be re accessed. At the SMA Negeri 1 Lubai Library, the process of accessing books is still manually, namely by searching for and reading books available in the SMA Negeri 1 Lubai Library. Researchers used qualitative descriptive methods to collect data, including direct observation, interviews, literature studies, and documentation. So, the data obtained shows that having no access makes it easier for students to read books online. The results of this research are a web-based e-library information system design expected to help resolve the obstacles that occur. Using an e-library information system can help library staff and students obtain and manage book collections carefully, precisely, and in a faster time. The Model View Controller (MVC) method is used with the Unified Modeling Language (UML) system modeling tools to design this system. This system was created using the PHP language and MySQL database server.